Evaluation of Participants' Experience in Farm to Peak Educational Gastronomy Activity Exploring Flavors and Nature' - Anissa Aulia Rahmasari; Reyfan Triansyah Wiriadi; Naufal Daffa Firdaus; Dewi Turgarini; ⁠Caria Ningsih (Jurnal Kewirausahaan dan Bisnis, 2026)
The success of a tourist destination is no longer measured solely by the quality of physical facilities, but by the depth of emotional experiences and the meaning obtained by tourists. Educational gastronomic tourism serves as a medium that connects tourists with nature and local culture through the integration of sensory activities. This study aims to evaluate the experience of participants in the Farm to Peak – Exploring Flavors and Nature activity in Wangunharja Village, Lembang, as a form of educational gastronomic tourism based on the farm to table concept. Using a mixed methods approach with a sequential explanatory design, this study combines quantitative data from 15 respondents through a Likert scale questionnaire as well as qualitative data from semi-structured interviews with activity organizers. The results of the descriptive analysis showed that all indicators measured, namely Customer Experience, Perceived Value, Behavior Intention, and Gastronomy Tourism Experience, obtained an average score above 4.20, which means that they were in the very high category. The qualitative findings reinforce these results by showing that the success of participants' experiences comes not only from physical and culinary activities, but also from interpersonal interactions, cultural narratives, and emotional visual documentation. This research emphasizes the importance of a holistic approach in creating meaningful and sustainable tourism experiences, and recommends a collaborative model between local communities and tourism actors for the development of value-based gastronomic tourism.Keywords: behavioral intentions; educative gastronomy; farm to table; perceived value; sustainable tourism; tourist experience